2010
DOI: 10.1051/0004-6361/200913610
|View full text |Cite
|
Sign up to set email alerts
|

The peculiar nova V1309 Scorpii/nova Scorpii 2008

Abstract: Aims. Nova Scorpii 2008 was the target of our Director Discretionary Time proposal at VLT+UVES in order to study the evolution, origin and abundances of the heavy-element absorption system recently discovered in 80% of classical novae in outburst. Methods. The early decline of nova Scorpii 2008 was monitored with high resolution echelle spectroscopy at 5 different epochs. The analysis of the absorption and the emission lines show many unusual characteristics. Results. Nova Scorpii 2008 is confirmed to differ f… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
158
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 116 publications
(174 citation statements)
references
References 38 publications
15
158
1
Order By: Relevance
“…The subsequent evolution, however, showed that as pointed out in Mason et al (2010), this was not a typical classical nova.…”
Section: V1309 Scorpiimentioning
confidence: 78%
See 4 more Smart Citations
“…The subsequent evolution, however, showed that as pointed out in Mason et al (2010), this was not a typical classical nova.…”
Section: V1309 Scorpiimentioning
confidence: 78%
“…Apart form V838 Mon, in our Galaxy the class also includes V4332 Sgr, whose outburst was observed in 1994 (Martini et al 1999), and V1309 Sco, which erupted in 2008 (Mason et al 2010). As extragalactic eruptions of this kind one can mention M 31 RV (eruption in 1989, Mould et al 1990), M 85 OT2006 (Kulkarni et al 2007), and NGC300 OT2008 (Berger et al 2009).…”
Section: Introductionmentioning
confidence: 90%
See 3 more Smart Citations